Exploration for a knowledge translation model in public dissemination via social media: Insights from an innovative Cochrane evidence dissemination competition in China - Yifei Song; Yusi Suo; Huikai Hu; Judith Deppe; Yanling Shen; Duanhong Yang; Ruoying Cai; Xuefeng Wang; Jin Zhang; Yutong Fei; Jianping Liu; Xun Li (Digital Health)
Objective This study aimed to present and evaluate an innovative evidence dissemination competition based on Cochrane evidence through participants’ perceptions, barriers, and feedback about evidence dissemination. Methods We evaluated competition participation, the submissions and their dissemination on social media. An online questionnaire was also conducted to analyze participants’ perceptions, barriers, and feedback about the competition and evidence dissemination. Microsoft Excel and IBM SPSS (26.0) were used to analyze the data. Results A total of 80 text-graphics and 14 short videos submissions in 10 dissemination formats were created by 173 participants. Once disseminated on WeChat, submissions received considerable attention. Questionnaires received revealed the most chosen motivations for participation in personal skills development, including “furthering studies in EBM” (60.7%, 105/173). Previous works (64.2%, 108/173) and social media information (53.2%, 92/173) were the main sources of inspiration. Lack of knowledge in clinical trials was the most prevalent barriers. Only few participants (medical background: 12.9%, nonmedical background: 18.3%) could understand the original English version without translation. Suggested improvement for the competition included “increase competition impact,” while expectations for future evidence dissemination included “disseminate through more social media platforms.” Conclusions The third Cochrane Dissemination Competition provided a valuable opportunity for participants to demonstrate their creativity while deepening their understanding of medical evidence, representing a successful attempt to disseminate high-quality Cochrane evidence to the public via Chinese social media. Key elements identified provide valuable insights for evidence dissemination to the public by health professionals via social media.